The Influence of Corporate Social Responsibility (CSR) Disclosure Towards Company Stock Return Moderated By Profit - Murdiono, A (KnE Social Sciences, 2018)
This study aims to empirically test and prove the influence of Corporate Social Responsibility (CSR) Disclosure towards the stock return in a company. The population of the study is listed in LQ 45 Indonesia Stock Exchange observed in 2013. The sample is taken by applying purposive sampling method and 36 companies become the samples. The analysis of inferential statistic in this study employs Moderated Regression Analysis (MRA) with the residual test. The findings show that: 1) CSR Disclosure significantly influences stock return, 2) ROA and ROE variable do not moderate the influence CSR Disclosure towards a stock return. This study also results that CSR Disclosure is the most fundamental variable to predict stock return. Keywords: stock return, ROA, ROE, CSR Disclosure